2023
DOI: 10.3390/cancers15153831
|View full text |Cite
|
Sign up to set email alerts
|

Brain Re-Irradiation Robustly Accounting for Previously Delivered Dose

Abstract: (1) Background: The STRIDeR (Support Tool for Re-Irradiation Decisions guided by Radiobiology) planning pathway aims to facilitate anatomically appropriate and radiobiologically meaningful re-irradiation (reRT). This work evaluated the STRIDeR pathway for robustness compared to a more conservative manual pathway. (2) Methods: For ten high-grade glioma reRT patient cases, uncertainties were applied and cumulative doses re-summed. Geometric uncertainties of 3, 6 and 9 mm were applied to the background dose, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Although some previous studies have reported similar approaches for the evaluation of re-irradiation treatments, 19,20 few have incorporated such functionalities into re-irradiation planning using commercially available software. [3][4][5] For the fictitious RI scenario in this study, the three re-planning strategies performed equally well (Table 2, Figure 2, Figure 3a,b), which was expected due to the large distances between PTV and relevant OARs associated with RI treatments. 1 However, note the slightly elongated EQD2 distribution for reRT reduce compared to F I G U R E 3 Dose-volume histograms (DVHs) using dose and total equivalent dose in 2-Gy fraction (EQD2 tot ) for the three relapse scenarios-repeat irradiation (RI), re-irradiation type 1 (RIT1) and type 2 (RIT2).…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…Although some previous studies have reported similar approaches for the evaluation of re-irradiation treatments, 19,20 few have incorporated such functionalities into re-irradiation planning using commercially available software. [3][4][5] For the fictitious RI scenario in this study, the three re-planning strategies performed equally well (Table 2, Figure 2, Figure 3a,b), which was expected due to the large distances between PTV and relevant OARs associated with RI treatments. 1 However, note the slightly elongated EQD2 distribution for reRT reduce compared to F I G U R E 3 Dose-volume histograms (DVHs) using dose and total equivalent dose in 2-Gy fraction (EQD2 tot ) for the three relapse scenarios-repeat irradiation (RI), re-irradiation type 1 (RIT1) and type 2 (RIT2).…”
Section: Discussionmentioning
confidence: 53%
“…The use of EQD2 allows for dose summation of radiotherapy courses with different fractionation schedules and is often used for dose summations in re-irradiation treatments. 1,[3][4][5]10…”
Section: Re-irradiation Optimization Functionsmentioning
confidence: 99%
See 3 more Smart Citations